Perspectives of pressurized intraperitoneal aerosol chemotherapy in terms of primary ovarian cancer with peritoneal carcinomatosis treatment - A. S. Dzasokhov; A. A. Kostin; V. L. Astashov; A. V. Turiev; A. D. Uskov (Исследования и практика в медицине)
The relevance of the problem of increasing the effectiveness of standard treatment of ovarian cancer is determined by the following characteristics of the disease: high one‑year mortality, high recurrence rate and unsatisfactory results of their treatment. Peritoneal carcinomatosis in ovarian cancer occurs in 65–70 % of cases. The standard modern approach to the treatment of ovarian cancer is a combination of surgical treatment and systemic intravenous chemotherapy. At the same time, more than 70 % of ovarian cancer cases are first diagnosed at stages III–IV. However, despite the successes in the field of surgery and drug treatment, the five‑year survival rate is no more than 24 % at the III and 4.6 % at the IV stage of the disease. One of the frontiers of ovarian cancer resistance to therapy is peritoneal carcinomatosis. Its resistance to therapy is due to the low bioavailability of cytostatics in metastases on the peritoneum to almost zero. In order to increase bioavailability, various forms of intra‑abdominal chemotherapy are used. The technique of pressurized intraperitoneal aerosol chemotherapy (PIPAC) has a number of advantages over other methods of intra‑abdominal antitumor treatment. These advantages include the uniform distribution of cytostatics over the peritoneum, the absence of penetration of cytostatics beyond the peritoneum, which allows PIPAC to be combined with systemic chemotherapy, low trauma and good tolerability of the procedure. PIPAC was implemented into clinical practice in 2011, and since then has been widely used in a number of foreign and domestic clinics. The conducted studies confirm the safety of the technique and its effectiveness against peritoneal carcinomatosis. The data of multicenter studies and the analysis of available literature data, as well as the successful own experience of PIPAC use create prerequisites for investigating the effectiveness of intra‑abdominal aerosol chemotherapy under pressure in relation to peritoneal carcinomatosis in ovarian cancer.